Global burden of neck pain and its gender and regional inequalities from 1990 - 2021: a comprehensive analysis from the Global Burden of Disease Study 2021 - Haifeng Wu; Yue Li; Congying Zou; Weidong Guo; Feng Han; Guoshun Huang; Lin Sun (BMC Musculoskeletal Disorders)
Abstract Background Neck pain is a growing public health concern, no recent research has comprehensively examined its incidence and years lived with disability (YLDs) across different regions and genders. For the first time, this study aims to provide the most recent estimates on the global burden of neck pain between 1990 and 2021 obtained from the 2021 global burden of disease (GBD) database, focusing on regional and gender inequalities. We also predict future trends, highlighting its increasing impact on public health. Materials and methods The study was conducted retrospectively using publicly available data from the GBD 2021 database, acquired on August 20, 2024. The incidence and burden of neck pain were assessed using DisMod-MR 2.1. Data on incidence and years lived with disability (YLDs) rates per 100,000 people were obtained for countries, regions, ages, and sexes globally. Results In 2021, the global age-standardized rates for incidence, and YLDs of neck pain per 100,000 population was 519 (95% uncertainty interval, 408—633), and 242 (163—343) per 100,000 population, respectively. Joinpoint regression showed both rates demonstrated an overall increasing trend from 1990 to 2021 worldwide. Projections suggest a slight decline in these rates for the coming years. Women consistently showed a higher burden than men across all age groups. Regional analyses indicated that the Islamic Republic of Iran had the highest rates, whereas New Zealand had the lowest. Negative correlations were observed between the Estimated Annual Percentage Change (EAPC) and both the age-standardized rates and the Sociodemographic Index (SDI). Low-SDI countries generally exhibited higher incidence and YLDs rates, whereas high-SDI countries maintained higher YLDs rates despite relatively lower incidence rates. Conclusion The global burden of neck pain increased between 1990 and 2021, but future projections indicate a potential mild decrease. Gender and regional inequalities persist, underscoring the need for targeted policy interventions focusing on women and low-SDI regions to alleviate the burden of neck pain.